On self-dual cyclic codes of length pa over GR(p2,s) - Jitman, Somphong (2017)
In this paper, cyclic codes over the Galois ring GR(p2,s) are studied. The main result is the characterization and enumeration of Hermitian self-dual cyclic codes of length pa over GR(p2,s). Combining with some known results and the standard Discrete Fourier Transform decomposition, we arrive at the characterization and enumeration of Euclidean self-dual cyclic codes of any length over GR(p2,s).